Ganoderma lucidum polysaccharides associated with 5-Fluorouracil impair OSCC tumorigenesis in vitro - Marcela Rodrigues de Camargo; Kelly Karina Inacio; Talita Fonseca Frazon; Nádia Ghinelli Amôr; Lígia Espoliar Corrêa; Flavia Cristina Costa; Emmanuelle Nascimento Quagliato; Camila Oliveira Rodini; Vanessa Soares Lara (Elsevier, 2023)
Backgrounds: Ganoderma lucidum polysaccharides have been shown several anti-cancer, anti-inflammatory, and immunomodulatory properties among studies with different tumor models and its use with advanced and conventional combination therapies is a world trend. The administration of 5-Fluorouracil is already used as chemotherapy for many tumors and works on tumor remission; however, its adverse effects are still severe, impoverishing treatment and quality of life for patients. Cancer stem cells represent a subpopulation of cells with defense mechanisms against chemotherapy agents and are the main cause of relapses and metastases in cancer treatments. Also, the Epithelial-Mesenchymal Transition program increases properties related to tumor malignancy and mortality. In this scenario, the aim of the study is to evaluate the effects of Ganoderma lucidum polysaccharides in combination with 5-Fluorouracil on the subpopulation of cancer stem cells present in the human oral squamous carcinoma cell line SCC-9. Methods: SCC-9 cells were treated in vitro for 72 h with different 5-Fluorouracil low doses, associated or not with Ganoderma lucidum polysaccharides. Cells maintained with culture media or cisplatin were used as control. All the cells were evaluated for cytotoxicity, cancer stem cells, and Epithelial-Mesenchymal Transition properties. Results: The associated treatment avoided proliferation, delayed migration, slightly modified morphology of cells, increased apoptosis, decreased colony and blocked spheres formation, and downregulated cancer stem cells, Epithelial-Mesenchymal Transition, and ABC drug transporters expression. In addition, Ganoderma lucidum polysaccharides + 5-Fluorouracil changed the treated cells into a non-cancer stem cell phenotype, a characteristically not resistant and less proliferative population. The 5-Fluorouracil treatment alone showed remarkable modification in cellular morphology, apoptosis, and absence of holoclones; however, it upregulated the molecular expression of cancer stem cells' hallmarks. Conclusions: These findings demonstrate that combining Ganoderma lucidum polysaccharides with a low dose of 5-Fluorouracil is effective against oral squamous cell carcinoma in vitro by enhancing the cells' sensitivity to drugs and reducing the characteristics associated with cancer stem cells (CSCs). This suggests the possibility of reducing conventional chemotherapy doses and improving oral squamous cell carcinoma treatment. It also highlights the potential for this combination to be used as an adjunct in Complementary Alternative Medicine (CAM).